Utilização do Software GPSeq na Solução Rápida das Ambigüidades GPS no Posicionamento Relativo Cinemático de Bases Curtas - MACHADO, WAGNER CARRUPT; MONICO, JOÃO FRANCISCO GALERA (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> Centimeter level GPS positioning is based on the very precise carrier beat phase measurements. However, this observable is ambiguous by a number of whole cycles between the satellite and receiver antenna at the first epoch of data collecting, which is called the ambiguity. GPS ambiguities are introduced as parameters to be estimated in the observation equations. However, since they are integer numbers there is no standard techniques for solve them. One of the ways is to apply sequential conditional least-squares estimation together with integer search techniques. The ambiguity resolution can be divided in two steps: estimation and validation. The estimation is concerned with the computation of the ambiguities values. The validation step is used to infer if the estimated value can be accepted or not. From the last decade until nowadays ambiguity resolution has been one of the most important research topic in geodetic positioning and a several methods have been proposed. Special attention has been made about the fast ambiguity resolution. The aim of this paper is to investigate the ambiguity resolution in the context of relative kinematic positioning and its implementation in the GPSeq software, which is a GPS data processing software developed in academic environment. In this paper some experiments about kinematic processing are presented, whose results shown that the GPSeq solution is compatible on the centimeter level with Reliance software. The results also shown an inefficiency of the ratio and the difference between the quadratic form of the residuals of the second best and best solution tests in validating the ambiguity resolution in time limits of solution of the baselines processed.